Assessing the need for adaptive radiotherapy in head and neck cancer patients using an automatic planning tool - Alves, Natália de Sousa Rodrigues (2021)
Unbiased analysis of the impact of adaptive radiotherapy (ART) is necessary to evaluate dosimetric benefit and optimize clinics' workflows. The aim of the study was to assess the need for adaptive radiotherapy (ART) in head and neck (H&N) cancer patients using an automatic planning tool in a retrospective planning study.